Preoperative preparation of infected wounds of superficial tissues, using the method of hyperbaric oxygenation with the ozone-containing mixture - N. F. Chukhraiev; G. V. Terehov; M. V. Kostylіev; S. P. Galich; I. P. Dmytrenko; S. N. Titarenko; I. M. Savytska; A. F. Dzygal (Клінічна хірургія)
Preoperative preparation of infected wounds of superficial tissues, using the method of hyperbaric oxygenation with the ozone-containing mixture